Understanding carbon flux of a heterologous metabolic pathway in Escherichia coli for sustainable methyl methacrylate biosynthesis - Tilley, Clemency (2022)
Three thousand kilotons of methyl methacrylate (MMA) are produced each year. The polymer of MMA, also known as Perspex®, has become ubiquitous in applications from construction to medical technologies since it was first synthesised in 1936. Presently, MMA is exclusively manufactured via chemical synthesis from petrochemical feedstocks, 96% of which is acetone. However, in recent years biosynthesis of an MMA precursor, butyl methacrylate (BMA), has been demonstrated in Escherichia coli. This is characterised by the up-regulation of 2-ketoisovalerate production, followed by expression of heterologous branched-chain β-ketoacid dehydrogenase, acyl-CoA oxidase (ACX), and alcohol acyltransferase (AAT). Decoupling industrial MMA production from the petrochemical industry by achieving industrial fermentation of BMA would provide a green alternative to Perspex® at a time where a shift towards low carbon technologies is increasingly supported politically, economically, and societally.